2021
DOI: 10.1093/hmg/ddab076
|View full text |Cite
|
Sign up to set email alerts
|

Ap2s1 mutation causes hypercalcaemia in mice and impairs interaction between calcium-sensing receptor and adaptor protein-2

Abstract: Adaptor protein 2 (AP2), a heterotetrameric complex comprising AP2α, AP2β2, AP2μ2 and AP2σ2 subunits, is ubiquitously expressed and involved in endocytosis and trafficking of membrane proteins, such as the calcium-sensing receptor (CaSR), a G-protein coupled receptor that signals via Gα11. Mutations of CaSR, Gα11 and AP2σ2, encoded by AP2S1, cause familial hypocalciuric hypercalcaemia types 1–3 (FHH1–3), respectively. FHH3 patients have heterozygous AP2S1 missense Arg15 mutations (p.Arg15Cys, p.Arg15His or p.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Third, ap2s1 functions developmentally in a non-neuronal cell type to regulate acoustically-evoked behavior selection and response latency, as neither pan-neuronal, nor ubiquitous acute expression of ap2s1 were sufficient to rescue escape behavior selection bias or appropriate SLC latency. For example, ap2s1 is expressed in glial populations which could regulate formation of relevant synaptic connections (Ng et al, 2016), and also regulates PTH secretion and serum ion balance by endocrine cells (Hannan et al, 2021), allowing non-autonomous effects on circuits through altered hormone or ion levels during development. While we cannot exclude the possibility that transgene expression levels were too low to rescue behavior selection or latency despite being in the right location or time, these same individuals demonstrated robust rescue of SLC habituation so the data nonetheless dissociate the mechanism of SLC habituation from behavior selection and SLC latency modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, ap2s1 functions developmentally in a non-neuronal cell type to regulate acoustically-evoked behavior selection and response latency, as neither pan-neuronal, nor ubiquitous acute expression of ap2s1 were sufficient to rescue escape behavior selection bias or appropriate SLC latency. For example, ap2s1 is expressed in glial populations which could regulate formation of relevant synaptic connections (Ng et al, 2016), and also regulates PTH secretion and serum ion balance by endocrine cells (Hannan et al, 2021), allowing non-autonomous effects on circuits through altered hormone or ion levels during development. While we cannot exclude the possibility that transgene expression levels were too low to rescue behavior selection or latency despite being in the right location or time, these same individuals demonstrated robust rescue of SLC habituation so the data nonetheless dissociate the mechanism of SLC habituation from behavior selection and SLC latency modulation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients, the impact of these changes may well be mitigated by upregulation of expression of the CaSR, heterodimerization of the CaSR with other GPCRs, or other compensatory mechanisms. Evidence for potential compensatory mechanisms, arise from studies that have identified heterozygous mutations of G-protein subunit α 11 (Gα 11 ) and adaptor protein 2 (AP2) as causes for diseases FHH2 and FHH3 respectively [4,27]. Gα 11 mutations impair coupling with the upstream CaSR or the downstream phospholipase C, whereas AP2 mutations impair CaSR trafficking [4,27,28].…”
Section: Plos Onementioning
confidence: 99%
“…Evidence for potential compensatory mechanisms, arise from studies that have identified heterozygous mutations of G-protein subunit α 11 (Gα 11 ) and adaptor protein 2 (AP2) as causes for diseases FHH2 and FHH3 respectively [4,27]. Gα 11 mutations impair coupling with the upstream CaSR or the downstream phospholipase C, whereas AP2 mutations impair CaSR trafficking [4,27,28]. The importance of the multiple components in the process illustrates the complexity of calcium homeostasis.…”
Section: Plos Onementioning
confidence: 99%
“…Controlling the expression of AP2M1 was proposed as a potentially effective treatment for cystic fibrosis, a genetic disorder caused by defective cellular trafficking [126], demonstrating its potential as a target gene for diverse diseases. Finally, the small subunit AP2S1 was shown to be critical for cellular calcium-sensing receptor activity [127], and AP2S1 mutations were reported to result in familial hypocalciuric hypercalcemia type 3, which causes high calcium levels in the bloodstream [128] Notably, most studies involving AP2S1 were linked to this genetic disease [129][130][131][132][133][134][135]. To date, with the exception of this report, AP2S1 has only been detected during the screening of other AP2 subunits that affect obesity [88], which suggests that its major function is in the calcium-sensing pathway.…”
Section: Ap2 Complexmentioning
confidence: 99%